2003
DOI: 10.1117/12.486359
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet nitride LED fabrication for high-flux white LED

Abstract: The requirements for maximizing the external quantum efficiency of UV nitride LEDs are discussed. It is shown that as the chip wavelength progressively decreases, nitride epi growth on a sapphire substrate becomes advantageous in terms of light extraction. The epilayer requirements for UV LEDs dictate the growth of n-AlGaN, with increasing Al contents, and the growth of UV-transparent p-GaN. It is shown that MOCVD growth in a Emcore D-180 or Ganzilla reactor is ideal for meeting the stringent epilayer requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…6(b) shows the typical reverse characteristics of the VLEDs with both contacts. Venugopalan et al 10 reported that aging of LEDs fabricated with Ag contacts can cause a large increase in the leakage current as a result of lateral migration of Ag. Therefore, the improvement of the reverse characteristics of the ITO/Ni/AgCu/Pt contacts should be associated with the reduction of the Ag migration.…”
Section: Resultsmentioning
confidence: 99%
“…6(b) shows the typical reverse characteristics of the VLEDs with both contacts. Venugopalan et al 10 reported that aging of LEDs fabricated with Ag contacts can cause a large increase in the leakage current as a result of lateral migration of Ag. Therefore, the improvement of the reverse characteristics of the ITO/Ni/AgCu/Pt contacts should be associated with the reduction of the Ag migration.…”
Section: Resultsmentioning
confidence: 99%
“…7 shows the typical reverse characteristics of the VLEDs with both contacts. Venugopalan et al 16) reported that aging of LEDs fabricated with Ag contacts can cause a large increase in the leakage current as a result of lateral migration of Ag. Therefore, the improvement of the reverse characteristics of the ITO/Ni/AgCu/Pt contacts should be associated with the reduction of the Ag migration.…”
Section: Resultsmentioning
confidence: 99%
“…The reverse leakage current can be attributed to diffusion, recombination, tunnelling, and, when illuminated, the photocurrent in the space-charge region. There have been also some studies on nitride-based LEDs that attributed the leakage current to a high threading defect density of the devices [3, 4], metal migration [5], and surface diffusion [6]. However, in the case of nitride-based LEDs, tunnelling of electrons into the conduction band is the most likely cause of reverse leakage current because the other mechanisms are small in magnitude owing to a wide bandgap of nitride-based LEDs and have rather weak voltage dependence.…”
mentioning
confidence: 99%